Convergence rates and finite-dimensional approximation for a class of ill-posed variational inequalities - Nguen, Byong (Ukrains’kyi Matematychnyi Zhurnal, 1997)
The purpose of this paper is to investigate an operator version of Tikhonov regularization for a class of ill-posed variational inequalities under arbitrary perturbation operators. Aspects of convergence rate and finite-dimensional approximations are considered. An example in the theory of generalized eigenvectors is given for illustration.